IMPLEMENTASI BANTUAN PRODUKTIF USAHA MIKRO DI MASA PANDEMI SERTA DAMPAKNYA PADA PERKEMBANGAN USAHA DI KECAMATAN JOMBANG - Sa'adah, Lailatus; Kurniasari, Arti (Universitas Wiralodra, 2022)
The Sars-CoV-2 outbreak threatens not just public health, but also the country's economy, particularly the MSME sector. Productive Micro Business Support (BPUM) is one of the initiatives used as capital assistance for micro-enterprises affected by Sars-CoV-2, with funding of 2,400,000 provided by the Government of the Republic of Indonesia through the Ministry of Cooperatives and Micro Enterprises. This study intends to identify the implementation of productive aid for microbusinesses during the pandemic, the supporting and hindering variables, and the effect on business growth in Jombang District. In this study, the author used a qualitative methodology. The results of this study reveal that the program implementation has been proceeding pretty effectively; nonetheless, there is a lack of direct socialization from both the Cooperatives and SMEs Office and the Kelurahan/Village. There are factors supporting the positive socio-economic impact felt by BPUM recipients, such as increasing sales, increasing income, and increasing employees. The negative impacts include inappropriate use of funds, mismanagement of funds and creating a sense of dependence on government assistance.